Estimating Nitrate Leaching to Groundwater from Orchards: Comparing Crop Nitrogen Excess, Deep Vadose Zone Data‐Driven Estimates, and HYDRUS Modeling. Issue 11 (23rd February 2017) - Baram, S.; Couvreur, V.; Harter, T.; Read, M.; Brown, P.H.; Kandelous, M.; Smart, D.R.; Hopmans, J.W.
Abstract : Core Ideas: Leaching below the root zone is estimated based on eight sites of intensive vadose zone monitoring. Across methods N losses estimated at the annual orchard scale were in the same order of magnitude. Simple N mass balance provided a good proxy of the orchard scale annual N accumulation in the soil Under current BMP N load to groundwater is likely in the range of 60 to 100 kg N ha–1. Large spatial and temporal variability in water flow and N transport dynamics poses significant challenges to accurately estimating N losses form orchards. A 2‐yr study was conducted to explore nitrate (NO3 − ) leaching below the root zone of an almond [ Prunus dulcis (Mill.) D. A. Webb] orchard. Temporal changes in water content, pore water NO3 − concentrations and soil water potential were monitored within and below the root zone to a soil depth of 3 m at eight sites, which represented spatial variations in soil profiles within an almond orchard in California. Orchard monthly average NO3 − concentrations below the root zone ranged from 225 to 710 mg L −1 with mean annual concentration of 468 and 333 mg L −1 for the 2014 and 2015 growing seasons, respectively. Despite the huge variability in pore water NO3 − concentration between sites, the larger spatiotemporal scale N losses estimated at the annual orchard scale from surface N mass balance, vadose zone based water and N mass balance, flow calculations, and HYDRUS modeling were all on the same order of magnitude (80–240 kg N ha −1 yr −1 ). All methods indicated that most of the N losses occur early in the growing season (February–May) when fertilizer is applied to wet soil profiles. Simple mass balance (i.e., N load applied minus N load removed) provided a good proxy of the annual N accumulation in the soil profile at the orchard scale. Reduction of N losses at the orchard scale would require alternative fertigation and irrigation practices to decrease the difference between the N load removed and the N load applied to orchards.